2015
DOI: 10.4274/meandros.2492
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Hepatitis C Virus Genotypes in Patients with Chronic Hepatitis C Infection

Abstract: Amaç: Hepatit C virüsü (HCV), kronik hepatit, siroz ve hepatosellüler karsinoma yol açarak dünya çapında önemli bir sağlık sorunu olmaktadır. Dizi analizi çalışmaları ile HCV'nin 7 genotipi ve 100'den fazla alt tipi olduğu ortaya konmuştur. HCV genotip 1'in genotip 2 ve 3'e göre daha ciddi hastalık yaptığı ve tedaviye kalıcı yanıtın daha az olduğu bilinmektedir. Bu çalışmada, kronik hepatit C hastalarında genotip dağılımının belirlenmesi amaçlanmıştır. AbstractObjective: Hepatitis C virus (HCV) infection repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
3
1
2
Order By: Relevance
“…This retrospective study analyzed the genotypes and their distribution within the population of HCV positives detected in recent years in Aydin Province of Turkey. Compared with the previous data governing the years between 2007 and 2010, the rates for the genotypes 1 and 2 remained nearly the same, but the presentation of genotypes 3 and 4 exhibited significant rises in numbers . Especially, genotype 4 was detected for the first time.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This retrospective study analyzed the genotypes and their distribution within the population of HCV positives detected in recent years in Aydin Province of Turkey. Compared with the previous data governing the years between 2007 and 2010, the rates for the genotypes 1 and 2 remained nearly the same, but the presentation of genotypes 3 and 4 exhibited significant rises in numbers . Especially, genotype 4 was detected for the first time.…”
Section: Discussioncontrasting
confidence: 51%
“…Despite the lower prevalence, the rates of genotypes 3 and 4 have especially been increasing since 2007 . Based on screenings performed between the years 2007 and 2010, the prevalence rates of genotypes 1b, 1a, 2b, and 3 within the HCV‐infected population in the province of Aydin were previously reported as 72%, 18%, 2%, and 2%, respectively . In recent years, however, the genotypes indicated certain shifts.…”
mentioning
confidence: 99%
“…Genotype 1b is more common in Europe and Japan, while genotype 1a is more common in the United States [1] . Various studies conducted in Turkey have shown the prevalence of genotype 1b to be between 72% and 84% [13][14][15] . HCV genotype distribution among dialysis patients is similar [14,16] .…”
Section: Discussionmentioning
confidence: 99%
“…This alteration may be due to immigrants, touristic activities and different risk factors for HCV infection, as well as increased safety procedures in medical practice. Table 4 shows the results of some of the HCV genotyping studies in Turkey (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27).…”
Section: Discussionmentioning
confidence: 99%